Edema in pregnant women - possibility of physiotherapeutic treatment - Wawryków, Agata; Korabiusz, Katarzyna; Torbe`, Andrzej; Lubkowska, Anna (Journal of Education, Health and Sport, 2017)
Lymphedema is excessive, pathologic accumulation of lymph. During pregnancy, especially in the third trimester of the body women collect water supply. In addition, the increased amount of blood circulating and difficult is the outflow of the lower limbs as a result of oppression growing uterus on the iliac veins are the reason for the formation of edema. Emerging swellings do not always bear witness to the pathology of pregnancy. Slight swelling localized around: ankles and fingers and toes, if not accompanied by an increase in blood pressure, there are disturbing. As a rule, they disappear after a rest. There are many physiotherapeutic methods that reduce edema. They are intended primarily to drain the edema fluid from the tissues. Applied physiotherapy also prevents functional effects of edema and abolishes pain, which significantly improves patient quality of life. The International Lymphatic Association (Lymphatic Association) is the primary treatment for edema, which is a comprehensive treatment for the treatment of edema. This includes: manual lymphatic drainage, lymph drainage exercises, multilayer bandaging, skin care, and patient education.